Determination of in Vitro Cytotoxic Activity of new Chalcone-Phosphazene Compounds Bearing Indole and Imidazole Hetero Groups as Side Groups on A2780 and PC-3 Cancer Cell Lines - Sandal, Suleyman; Tekin, Suat; Koran, Kenan; Gorgulu, A. Orhan (Wiley, 2018)
[Abstract Not Available]